2019
DOI: 10.1590/0103-6440201901953
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Ethyl-Cyanoacrylate Coating Against Candida Albicans Biofilm Formation

Abstract: The aim of this study was to verify whether modifications made in a hard chairside reline resin by an ethyl-cyanoacrylate adhesive, ECA (Super Bonder®, Loctite, Itapevi, SP, Brazil) would be able to inhibit or reduce Candida albicans biofilm formation on its surface, comparing to a commercial surface sealant (BisCover®, Bisco, Schaumburg, USA). Reline resin specimens were fabricated and randomly divided into 6 groups (n=8): CG (control group), no surface treatment; ECA1, ECA coating on the surface before steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Among tested restorative materials, lower bacterial adhesion was observed with the application of BLV, which is an anti-adherent, low-viscosity, and ethanol-based sealant. Even though the effect of BLV against Candida albicans over dentures has been proven in many studies, 10,40 researches against the S. mutans biofilm on composite materials involving BLV are very rare. Furthermore, it appears that this is the first study to investigate the effect of BLV on bacterial adhesion of bulk-fill composites.…”
Section: S481mentioning
confidence: 99%
“…Among tested restorative materials, lower bacterial adhesion was observed with the application of BLV, which is an anti-adherent, low-viscosity, and ethanol-based sealant. Even though the effect of BLV against Candida albicans over dentures has been proven in many studies, 10,40 researches against the S. mutans biofilm on composite materials involving BLV are very rare. Furthermore, it appears that this is the first study to investigate the effect of BLV on bacterial adhesion of bulk-fill composites.…”
Section: S481mentioning
confidence: 99%
“…The cyanoacrylate adhesives evaluated in this study have been successfully used in surgical procedures, both in medicine and dentistry (Thakeb et al, 1995;Pascual et al, 2016) for the control of hemorrhages (Al-Bawardy et al, 2016). Recently, cyanoacrylates and fibrin biopolymers have also been studied for use as denture coating adhesives (Ali et al;Soon et al, 2015;Távora et al).…”
Section: Discussionmentioning
confidence: 99%
“…Authors have reported the coating of PMMA surfaces (Ali et al, 2013;Távora et al, 2019) In this context, the possibility of applying cyanoacrylate-based adhesives as coatings on acrylic resins was considered, thus modifying its surface properties, reducing roughness, and increasing hydrophobicity (Távora et al). However, no study has assessed its long-term efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…A new wound dressing system based on poly(lactic acid)‐modified cyanoacrylate that is easily removable has been proposed 8 . A useful effect of ethyl cyanoacrylate (ECA) coating reline resin surfaces has been described, suggesting a promising way to prevent fungal biofilm formation on dentures 9 . Recently, the efficacy of a polycyanoacrylate porous material for bone tissue substitution was demonstrated 10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 A useful effect of ethyl cyanoacrylate (ECA) coating reline resin surfaces has been described, suggesting a promising way to prevent fungal biofilm formation on dentures. 9 Recently, the efficacy of a polycyanoacrylate porous material for bone tissue substitution was demonstrated. 10 The monomers occur as clear and colorless liquids with low viscosity, high volatility and strong reactivity.…”
Section: Introductionmentioning
confidence: 99%